Prisoners’ Perceived Violence and Hair Regulation in Hong Kong Prisons: Gender-Based Differences - Lo, T. Wing; Hui, Cora Y. T.; Guan, Xin; Kwok, Sharon I. (Frontiers in Psychology, 2022)
Hair regulation is an essential policy for maintaining hygiene, security, and discipline in correctional institutions. However, the implementation of any hair-regulating policy should include a consideration of gender needs and differences. This study investigated Chinese prisoners’ perceived influence of hairstyles on their behavioral responses. Data were collected by means of a self-administered questionnaire survey from 500 male and 500 female prisoners in 11 correctional institutions of Hong Kong, China. Descriptive analyses and chi-square tests were used to explore the perceived violence of prisoners and gender differences. Mediation analysis was adopted to examine the prisoners’ perceived behavioral responses and mental and psychological well-being under different hairstyle situations, using self-esteem, procedural fairness, and negative emotional responses as mediators. The study found that male prisoners are inherently more tensive than the female group in terms of violent proclivities. In addition, perceived violent behavior is associated with hairstyle, and the influence path is gender related. Restrictive hair regulations that do not address unique social and cultural meanings and gender differences would decrease male prisoners’ self-esteem, while increasing all prisoners’ negative emotional responses and reducing their perceived procedural fairness. To maintain security inside institutions, we recommend short hair for male prisoners and long hair for female prisoners in Chinese prisons. Given that many prisons in Asian and African nations have an authoritarian style of governance similar to that of China, this study is of considerable international relevance.